Creación de valor público: un estudio desde la perspectiva de los stakeholders - Cifuentes-Martínez, Wilson Eduardo (2022)
Introduction: Nowadays, public value creation is a crucial topic in public sector issues. Previous research have shown that stakeholders play a critical role in the creation process but do not have enough empirical evidence to support this. Objective: This study identifies its components from a public organization’ stakeholders’ perception. Materials and methods: Data were collected through interviews using a semi structured questionnaire focused on identifying the value creation components using categories and subcategories. Results: All the stakeholders expressed the importance of their guidance and permanent feedback in the value co-creation with the public organization. Conclusions: A new category emerged and showed that communication with stakeholders influences the visibility and performance from the organization.